PEMBELAJARAN HOTS BERBASIS PENDEKATAN LINGKUNGAN DI SEKOLAH DASAR - Fathul Jannah; Radiansyah; Raihanah Sari; Reja Fahlevi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine the extent of the teacher's skills in planning and implementing HOTS learning based on an environmental approach. The research method used is descriptive qualitative. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation studies. The data collected were analyzed by data selection techniques, data tabulation, calculating alternative answers, then describing and analyzing the data. Based on the results of data analysis, it can be concluded that the implementation of HOTS learning based on an environmental approach in elementary schools in Banjar Regency, especially in Kertak Hanyar District, the High Class Gugus has not been fully implemented, this is because some teachers experience limitations in developing HOTS learning devices based on an environmental approach and sometimes experience problems obstacles in implementing HOTS learning based on an environmental approach. To compile the assessment in the form of HOTS is also constrained, because not all students are able to construct, understand, and apply their critical thinking skills, so the evaluation tool designed needs to be adapted to the needs of students.